If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -8) + -5 = 5(x + -3) + -5 Reorder the terms: 5(-8 + 2x) + -5 = 5(x + -3) + -5 (-8 * 5 + 2x * 5) + -5 = 5(x + -3) + -5 (-40 + 10x) + -5 = 5(x + -3) + -5 Reorder the terms: -40 + -5 + 10x = 5(x + -3) + -5 Combine like terms: -40 + -5 = -45 -45 + 10x = 5(x + -3) + -5 Reorder the terms: -45 + 10x = 5(-3 + x) + -5 -45 + 10x = (-3 * 5 + x * 5) + -5 -45 + 10x = (-15 + 5x) + -5 Reorder the terms: -45 + 10x = -15 + -5 + 5x Combine like terms: -15 + -5 = -20 -45 + 10x = -20 + 5x Solving -45 + 10x = -20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -45 + 10x + -5x = -20 + 5x + -5x Combine like terms: 10x + -5x = 5x -45 + 5x = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 -45 + 5x = -20 + 0 -45 + 5x = -20 Add '45' to each side of the equation. -45 + 45 + 5x = -20 + 45 Combine like terms: -45 + 45 = 0 0 + 5x = -20 + 45 5x = -20 + 45 Combine like terms: -20 + 45 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| 16+3s-2s=24+24-20 | | 5-8(4x-4)=-7 | | 3(x+2)=6(x-1)+6 | | -16=y-13 | | 60-.04x=80 | | 3/10-(-2/3) | | -3=z-18 | | 30+3*x-2*(12-x)=38 | | 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 | | n/4-5=17 | | 5(x+6)-(x+28)=-2x | | f(x)=x-9/X^2-16 | | 8x+2=6x+36 | | 8(3x-4)=14x-2 | | 17x-9x=24 | | 5x-(2x+9)=9 | | -97x+42x= | | 6(7x-6)=27 | | 15-6x=-51 | | c+1.7=2.6 | | 96-3x=8 | | -6i+4= | | 6x-17=-107 | | 5(x-6)-(x+28)=-2x |